The Cladosporium Fulvum Bap1 Gene: Evidence for a Novel Class of Yap-related Transcription Factors with Ankyrin Repeats in Phytopathogenic Fungi - Bussink, H-J.; Clark, A.; Oliver, Richard (2001)
The Saccharomyces cerevisiae transcription factor gene YAP1 is a key regulatory gene conferring resistance against oxidative stress and various cytotoxic compounds. It would be of interest to isolate homologous genes in pathogenic fungi as candidate pathogenicity genes. We have developed a generally applicable hybridization method, using a single degenerate oligonucleotide probe designed on the basis of the conserved DNA-binding region of yAP1 homologs in yeast species, to clone a related gene, Bap1, from the tomato pathogen, Cladosporium fulvum. This gene has the capacity to code for a possible transcription factor consisting of an N-terminal, yAP1-related, basic DNA-binding domain. It lacks an obvious downstream leucine zipper but includes C-terminal ankyrin-like repeats. The Cochliobolus carbonum pathogenicity factor TOXEp shows a similar modular structure. BAP1 and TOXEp appear to represent a novel fungus-specific class of Yap basic DNA-binding domain-type transcription factors with ankyrin-like repeats (bANK proteins) in phytopathogenic fungi. A possible role of BAP1 in a membrane transporter-mediated detoxification or secretion process is discussed.